POTENSI ACTINOMYCETES DARI RHIZOSFER TUMBUHAN DI EKOSISTEM KARST GORONTALO SEBAGAI ANTICANDIDA - Riskanarti K. Lihaawa; Yuliana Retnowati; Abubakar Sidik Katili (Jurnal Humaniora & Sosial Sains, 2025)
Karst ecosystem is one of the extreme marginal areas or types of soil that has low soil fertility. Soil in the karst ecosystem has a relatively high calcium (Ca) content which can affect the availability of phosphorus (P). However, there is microbial activity that can provide nutrient needs for plants to stay alive, one of which is Actinomycetes. This research method uses a quantitative research method, rhizosphere soil samples were taken at three locations, namely Bangga hill, Panipi hill around Lake Limboto, and Olohuta hill with a purposive sampling method. The results of the study showed that there were 7 isolates of Actinomycetes found associated with 5 types of plants in the karst ecosystem. Actinomycetes isolates showed almost uniform morphological, colony and cell characteristics dominated by white. The results of the anticandida activity test showed that there were 2 isolates (KSLl and KSIc) that inhibited the growth of Candida albicans, KSLl with an inhibition zone diameter of 10.5 mm and KSIc with an inhibition zone diameter of 17.5 mm. Molecular identification based on 16S RRNA gene sequences showed that the KSLl isolate was closely related to Streptomyces aegyptia with a similarity index of 99.64% and the KSIc isolate was closely related to Istreptomyces sp with a similarity index of 99.57%.